Autoantibodies elicited with SARS-CoV-2 infection are linked to alterations in double negative B cells - Castleman, Moriah J.; Stumpf, Megan M.; Therrien, Nicholas R.; Smith, Mia J.; Lesteberg, Kelsey E.; Palmer, Brent E.; Maloney, James P.; Janssen, William J.; Mould, Kara J.; Beckham, J. David; Pelanda, Roberta; Torres, Raul M. (Frontiers in Immunology, 2022)
Double negative (DN) B cells (CD27-IgD-) comprise a heterogenous population of DN1, DN2, and the recently described DN3 and DN4 subsets. In autoimmune disease, DN2 cells are reported to be precursors to autoreactive antibody secreting cells and expansion of DN2 cells is linked to elevated interferon levels. Severe SARS-CoV-2 infection is characterized by elevated systemic levels of pro-inflammatory cytokines and serum autoantibodies and expansion of the DN2 subset in severe SARS-CoV-2 infection has been reported. However, the activation status, functional capacity and contribution to virally-induced autoantibody production by DN subsets is not established. Here, we validate the finding that severe SARS-CoV-2 infection is associated with a reduction in the frequency of DN1 cells coinciding with an increase in the frequency of DN2 and DN3 cells. We further demonstrate that with severe viral infection DN subsets are at a heightened level of activation, display changes in immunoglobulin class isotype frequency and have functional BCR signaling. Increases in overall systemic inflammation (CRP), as well as specific pro-inflammatory cytokines (TNFα, IL-6, IFNγ, IL-1β), significantly correlate with the skewing of DN1, DN2 and DN3 subsets during severe SARS-CoV-2 infection. Importantly, the reduction in DN1 cell frequency and expansion of the DN3 population during severe infection significantly correlates with increased levels of serum autoantibodies. Thus, systemic inflammation during SARS-CoV-2 infection drives changes in Double Negative subset frequency, likely impacting their contribution to generation of autoreactive antibodies.